Wskaźnik określeń werbalnych w stylistycznej charakterystyce współczesnych reportaży (na tle porównawczym) - Ostrowska, Katarzyna; Ruszkowski, Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The verbal definitions index, along with other indicators such as the nominalism index, epithetization index, quantitative richness of vocabulary and repetition of vocabulary, is a useful parameter in the stylistic characterization of the text. It is calculated by dividing the sum of adverb uses by the sum of verb uses ( ). It determines how many adverbs there are for one verb. The aim of the proposed article is to determine the index of verbal terms for contemporary Polish reportage against a comparative background of twenty-three different types of texts, based on calculations contained in the linguistic works of I. Kamińska-Szmaj, W. Pisarek, M. Rachwałowa, M. Zarębina. In order to do this, a three-stage methodology was used, including: corpus, quantitative and comparative analyses. The corpus of texts representative of contemporary Polish reportage is a selection of eighteen reportage novels awarded with the Beata Pawlak Award. The analysis carried out showed quite high homogeneity of the examined reportages in terms of the analyzed feature – the extreme values differ only by 0.17, and the deviations from the calculated average (Ww = 0.31) do not exceed 0.10 in any of the reportages.